Категорія топологічних джет-многовидів та деякі застосування в теорії нелінійних нескінченновимірних динамічних систем - Прикарпатський, А.К.; Філь, Б.Н. (Український математичний журнал, 1992)
С целью исследования точных конечномерных аппроксимаций нелинейных динамических систем на бесконечномерных функциональных многообразиях предлагается новая катгория топологических джет-многообразий. Изучаются дифференциально-геометрические структуры на них и их приложения в теории интегрируемости в квадратурах нелинейных динамических систем типа Лакса. A new category of topological jet manifolds is proposed for the purpose of investigating exact finite-dimensional approximations of nonlinear dynamical systems on infinite-dimensional functional manifolds. Differential geometry structures on these manifolds and their applications to the theory of integrability in quadratures of nonlinear dynamical Lax-type systems are studied.